Equity Structure, Strategic Investment Psychology, and Performance in China’s Green Economy Context - Guo, Li Xin; Lin, Kuen-Lin; Zhang, Li-Ting; Liu, Chi-Fang (Frontiers in Psychology, 2021)
• This study empirically tests the impacts of equity structure on strategic investment psychology in green affairs in R&D versus Marketing dimensions and company performance. Based on data from Chinese high-tech industry listed companies, the empirical results show that: (1)the largest shareholder's shareholding ratio has a positive effect on marketing investment psychology and a negative impact on R&D investment psychology, (2) other large shareholders’ shareholding ratio are positive related to R&D investment psychology;（3） R&D investment psychology has a negative effect and marketing investment psychology has a positive influence on the current performance; (4) equity counterbalance is positive related to R&D investment psychology and has a negative effect on the current performance. This study contributes to the literature of corporate governance on sustainability issue by providing a new psychological perspective. The results also provide an important guidance for the corporate governance practice in green economies.